2022
DOI: 10.1007/s43630-022-00244-w
|View full text |Cite
|
Sign up to set email alerts
|

Acetal photocatalytic formation from ethanol in the presence of TiO2 rutile and anatase

Abstract: The decomposition of ethanol, one of the most important biomass platform molecules, was investigated under green conditions, ambient temperature, atmospheric pressure and air for the synthesis of acetal in the presence of TiO 2 activated under UV-A radiation. The impact of ethanol concentration, of the nature of TiO 2 (rutile, anatase or mixture), of the photodeposition of Pt under air or argon were all factors under investigation. Whatever the conditions and the nature of catalyst used, acetaldehyde was initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Therefore, only recently avoiding the use of acids, green solid photocatalytic systems have increasingly been employed to catalyse such transformations in tandem fashion [12,17,22–25] . Also, photocatalytic conversion of aldehyde to acetal with ethanol using TiO 2 and other photocatalysts has shown significant promise [23,25–27] . Nikitas et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, only recently avoiding the use of acids, green solid photocatalytic systems have increasingly been employed to catalyse such transformations in tandem fashion [12,17,22–25] . Also, photocatalytic conversion of aldehyde to acetal with ethanol using TiO 2 and other photocatalysts has shown significant promise [23,25–27] . Nikitas et al.…”
Section: Introductionmentioning
confidence: 99%
“…[12,17,[22][23][24][25] Also, photocatalytic conversion of aldehyde to acetal with ethanol using TiO 2 and other photocatalysts has shown significant promise. [23,[25][26][27] Nikitas et al showed that thioxanthenone photocatalysts efficiently catalyzed the acetalization of aldehydes using a household lamp. [16] Similarly, Subramanian et al achieved chemoselective acetalization with Ni (II) complexes under neutral conditions.…”
Section: Introductionmentioning
confidence: 99%